Neuroprotective Effect of Ruscogenin against Cognitive Impairment on Pentylenetetrazole-induced Epileptic Seizures in Rats - Ma, Qiaoli; Almoallim, Hesham S.; Alharbi, Sulaiman Ali; Rengarajan, Thamaraiselvan (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Epilepsy, which affects about 1% of the world's population, is the third most common neurological disease after stroke and Alzheimer's disease. It is characterized by recurrent spontaneous seizures due to abnormal neuronal excitability and hypersynchrony. Objectives: The current work was aimed at discovering the neuroprotective properties of ruscogenin against Pentylenetetrazole (PTZ)-induced epilepsy in rats. Materials and Methods: The epileptic episode was induced in the rats by injecting 45 mg/kg of PTZ. Rats were pretreated with 10 mg/kg of ruscogenin 30 min before the PTZ challenge. The seizure severity and latency were assessed in the control and experimental rats. The status of oxidative markers, inflammatory cytokines, and neurotransmitters was examined using the corresponding assay kits. The histopathological analysis was done on the brain tissues of the experimental rats. The viability of control and treated neural SHSY-5Y cells was assessed with the MTT assay. Results: The ruscogenin treatment effectively reduced the seizure severity and augmented the latency in the epilepsy rats. The levels of Nitric Oxide (NO) and NO syntheses were effectively reduced in the brain tissues of epilepsy rats by the ruscogenin treatment. Ruscogenin decreased the oxidative index and increased the antioxidant index in the brain tissues of epilepsy rats. The levels of neurotransmitters were increased, and inflammatory cytokines were decreased in the epileptic rats by the ruscogenin. The results of histopathological analysis demonstrated the neuroprotective effects of ruscogenin. The viability of PTZ-challenged neural SHSY-5Y cells was increased by the ruscogenin treatment. Conclusion: In conclusion, the current results revealed that pretreatment with ruscogenin decreased the PTZ-induced epilepsy in rats by exerting its antioxidant and anti-inflammatory effects. Therefore, it may be concluded that ruscogenin may be a possible therapeutic option to treat epilepsy.
Keywords: Seizure; Gammaaminobutyric acid; Nitric oxide synthase; Ruscogenin; SHSY-5Y cells